Vi-Vaccinations Induce Heterogeneous Plasma Cell Responses That Associate With Protection From Typhoid Fever - Cross, Deborah L.; Verheul, Marije K.; Leipold, Michael D.; Obermoser, Gerlinde; Jin, Celina; Jones, Elizabeth; Starr, Joshua S.; Mohorianu, Irina; Blohmke, Christoph J.; Maecker, Holden T.; Napolitani, Giorgio; Hill, Jennifer; et al. (Frontiers in Immunology, 2020)
Vi-polysaccharide conjugate vaccines are efficacious against cases of typhoid fever; however, an absolute correlate of protection is not established. In this study, we investigated the leukocyte response to a Vi-tetanus toxoid conjugate vaccine (Vi-TT) in comparison with a plain polysaccharide vaccine (Vi-PS) in healthy adults subsequently challenged with Salmonella Typhi. Immunological responses and their association with challenge outcome was assessed by mass cytometry and Vi-ELISpot assay. Immunisation induced significant expansion of plasma cells in both vaccines with modest T follicular helper cell responses detectable after Vi-TT only. The Vi-specific IgG and IgM B cell response was considerably greater in magnitude in Vi-TT recipients. Intriguingly, a significant increase in a subset of IgA+ plasma cells expressing mucosal migratory markers α4β7 and CCR10 was observed in both vaccine groups, suggesting a gut-tropic, mucosal response is induced by Vi-vaccination. IgA+ plasma cells with mucosal migratory markers more associated with protection from typhoid fever in Vi-PS vaccinees but not Vi-TT. Conversely, the IgA- fraction of the plasma cell response was only associated with protection in Vi-TT. This suggests these vaccines rely on differential means of protection in vaccinated indviduals. In summary, these data indicate that a phenotypically heterogeneous response including both gut-homing and systemic antibody secreting cells may be critical for protection induced by Vi-TT vaccination.